PENGARUH PENEMPATAN KERJA DAN BEBAN KERJA TERHADAP PRESTASI KARYAWAN PADA PT IR STRUKTUR PAPUA KOTA SORONG - Sofia, Susetyowati; Rokhimah, Rokhimah; Marnianti, Marnianti (LP2M Universitas Bina Bangsa, 2024)
This study aims to determine whether Job Placement and Workload affect Employee Performance at PT. IR Structure Papua Sorong City. This study used descriptive and correlation methods using quantitative approaches. The population of this study was employees working at PT. IR Papua structure of Sorong city numbered 35 people. The collection technique until this study used a saturated sample with a sample of 35 people. The data analysis method uses multiple linear analysis, hypothesis testing (t test, f test and determination test). The primary data of this study was obtained by distributing questionnaires to respondents using a measurement scale, namely the Likert scale. Researchers conducted primary testing in this study using the SPSS Version 20 application program for windows. The results of the multiple regression analysis that has been carried out obtained Y = 6.035 + 0.860 X1 + 0.830 X2. The results of the t test obtained the results of the X1 tcount value of 6.197 and the results of the X2 tcount value of 5.960, the X1 coefficient value of 0.860, the X2 coefficient value of 0.830 and the X1 significance value of 0.000, the significance value of 0.000 means that the variables of job placement and Workload have a positive and significant effect on Employee Work Performance. In the coefficient of determination (R2) test, the results obtained were 0.584 (58.4%), which means that the variables of Job Placement and Workload are influenced by the variable of Employee Job Placement 58.4%, while the remaining 41.6% is influenced by other factors from outside this study